Tinjauan Utilitarianisme Hukum Atas Penerapan Regulasi Uang Kuliah Tunggal (UKT) di Perguruan Tinggi Keagamaan Islam Negeri - Purnomo, Agus; Saifullah, Saifullah (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
This paper examines the benefits of changing the payment system from SPMA (Academic Quality Improvement Contribution) to UKT (Single Money). On the one hand, the government considers that the UKT system provides great benefits because it is able to provide access to higher education for the general public who are less well off. On the other hand, students considered that the UKT system was not as good as theorized because it did not provide significant benefits. With a legal approach to UKT regulation, it is analyzed with Jeremy Bentham's theory of utilitarianism by using UKT implementation data in several PTKIN. As a result, the UKT system has benefits for the community. By using the instrument of the principle of utilitarianism, namely the greatest happiness, the data in the field shows that the implementation of UKT provides benefits to students.